Control algorithms of shunt active power filter for harmonics mitigation: a review - Hoon, Yap; Mohd Radzi, Mohd Amran; Hassan, Mohd Khair; Mailah, Nashiren Farzilah (MDPI, 2017)
Current harmonics is one of the most significant power quality issues which has attractedtremendous research interest. Shunt active power filter (SAPF) is the best solution to minimizeharmonic contamination, but its effectiveness is strictly dependent on how quickly and accuratelyits control algorithms can perform. This manuscript reviews various types of existing controlalgorithms which have been employed for controlling operation of SAPF. Harmonic extraction,DC-link capacitor voltage regulation, current control and synchronizer algorithms are examinedand discussed. The most relevant techniques which have been applied for each control algorithmare described and contrasted in an organized manner to identify their respective strengths andweaknesses. It is found that the applied control algorithms differ in two conditions: (1) the conditionwhere harmonic current distortion is treated by the SAPF in the presence of non-ideal source voltage;and (2) the condition where multilevel inverter is employed as the circuit topology of SAPF.